Pre–emption right of shareholders to purchase shares for sale in private limited liability companies: the problematic legal remedies - Bitė, Virginijus; Narkevičius, Žygimantas (Business: Theory and Practice, 2016)
This article analyses the problems that can arise when implementing the rights of shareholders in private limited liability companies to purchase the shares of another shareholder being for sale in priority to others and the possible legal remedies for violated rights. According to the practice of the Lithuanian Supreme Court, the rights of the buyer cannot be assigned to a private limited liability company shareholder whose pre-emption right to purchase the shares being for sale has been breached. However, in this article it is being argued that perhaps in certain exceptional cases, in order to create fair business practice and ensure a “tangible” result for the plaintiff in relation to the judgment, the court could (should) take advantage of the freedom to maneuver and, by implementing justice, change the method of restitution (pertaining to the subject) – assign the shares to the plaintiff (an aggrieved shareholder) simultaneously creating an obligation on the same person to settle properly with the last owner of the disputed shares.